1990
DOI: 10.2307/2008503
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Birkhoff Type Quadrature Formulae

Abstract: Abstract. The classical approach to the theory of quadrature formulae is based on the concept of algebraic degree of precision (ADP). A quadrature formula ß, is considered to be "better" than Q2 if ADP(g, ) > ADP(ß2). However, there are many quadratures that use the same number of evaluations of the integrand and have the same ADP. Then, how should one compare such formulae? We show in this paper that the error of the quadrature depends monotonically on the type of data used. Roughly speaking, the lower the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In another paper, he showed in [11] that the formulas introduced in [9] are unique. Bojanov and Nikolov [12] showed that the error of the quadrature formulas depends monotonically on the data. Wang and Guo [13] obtained the asymptotic estimate of nodes and weights of Gaussian-Lobatto-Legendre-Birkhoff quadrature formulas.…”
Section: Introductionmentioning
confidence: 99%
“…In another paper, he showed in [11] that the formulas introduced in [9] are unique. Bojanov and Nikolov [12] showed that the error of the quadrature formulas depends monotonically on the data. Wang and Guo [13] obtained the asymptotic estimate of nodes and weights of Gaussian-Lobatto-Legendre-Birkhoff quadrature formulas.…”
Section: Introductionmentioning
confidence: 99%